The effect of garlic intake on glycemic control in humans: a systematic review and meta-analysis - Emami, Shaghayegh; Rouhani, Mohammad Hossein; Azadbakht, Leila (Progress in Nutrition, 2017)
Objective: To conduct a systematic review and meta-analysis of the effects of garlic intake on glycemic control in humans. Methods: We searched MEDLINE, EMBASE, EBSCO, and Science Direct as international data bases, and IranMedex, Magiran, and SID as local databases for studies on effect of garlic intake on glycemic control in humans published until March 2015.  Our search included MeSH and non-MeSH terms.The quality of included studies was assessed using the Jadad scale.  Results: Ten articles were eligible for current meta-analysis. The results showed that garlic intake could decrease fasting blood sugar (FBS) (P